Advances in catalysis and related subjects. - Eley, D. D.; Selwood, P. W. (Pierce Wilson), 1905-1986; Weisz, Paul Burg, 1919- (Advances in catalysis and related subjects, 1959)
ADVANCES IN CATALYSIS VOLUME 11.